2008
DOI: 10.1111/j.1365-2486.2008.01555.x
|View full text |Cite
|
Sign up to set email alerts
|

Acclimation to temperature and temperature sensitivity of metabolism by ectomycorrhizal fungi

Abstract: Ectomycorrhizal (ECM) fungi contribute significantly to ecosystem respiration, but little research has addressed the effect of temperature on ECM fungal respiration. Some plants have the ability to acclimate to temperature such that long-term exposure to warmer conditions slows respiration at a given measurement temperature and long-term exposure to cooler conditions increases respiration at a given measurement temperature. We examined acclimation to temperature and temperature sensitivity (Q 10 ) of respirati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
83
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(84 citation statements)
references
References 59 publications
1
83
0
Order By: Relevance
“…Since the respiration activity of C. geophilum ectomycorrhizae has been reported to be significantly less altered than that of Lactarius sp., C. geophilum was suggested to better maintain the physiological integrity of beech roots facing drought stress (Jany et al 2002). In contrast, under high temperatures, a decreased colonization with C. geophilum has been detected in Quercus myrsinaefolia (Kasai et al 2000), agreeing with the observation of its reduced respiration under increasing temperature (Malcolm et al 2008). In any case, C. geophilum being a hydrophilic and short-distance exploration fungus has been suggested as a potential indicator of environmental changes (reviewed by Lehto and Zwiazek 2011).…”
Section: Fagaceae Mycorrhization In a Mediterraneanmentioning
confidence: 65%
“…Since the respiration activity of C. geophilum ectomycorrhizae has been reported to be significantly less altered than that of Lactarius sp., C. geophilum was suggested to better maintain the physiological integrity of beech roots facing drought stress (Jany et al 2002). In contrast, under high temperatures, a decreased colonization with C. geophilum has been detected in Quercus myrsinaefolia (Kasai et al 2000), agreeing with the observation of its reduced respiration under increasing temperature (Malcolm et al 2008). In any case, C. geophilum being a hydrophilic and short-distance exploration fungus has been suggested as a potential indicator of environmental changes (reviewed by Lehto and Zwiazek 2011).…”
Section: Fagaceae Mycorrhization In a Mediterraneanmentioning
confidence: 65%
“…However, they can also exist in separation from their host trees and gain carbon by heterotrophic decomposition of plant litter and soil organic matter (Nehls 2008;Treseder et al 2007;Malcolm et al 2008). Genome analysis revealed that almost the whole suite of genes for saprophytic enzymes was present in Laccaria bicolor, a typical EM fungus of the basidiomycetes (Martin et al 2008).…”
Section: Introductionmentioning
confidence: 97%
“…Baath and Wallander (2003), Hawkes et al (2008), andMalcom et al (2008) reported increased respiration of EM as a response to increased temperatures. However, some species show a fast temperature acclimation and reduce respiration after days or weeks (Heinemeyer et al 2007;Malcolm et al 2008). In consequence, this would lead to a C accumulation in hyphae when C is still supplied at higher rate to the fungus.…”
Section: Introductionmentioning
confidence: 98%
“…Recent evidence from empirical studies suggests that microbial abundance and community composition are highly sensitive to environmental changes, such as warming, N addition, and altered precipitation (Allison and Martiny 2008;Hawkes et al 2011). Furthermore, microbial communities may shift in composition, adapt physiologically, or evolve in response to new conditions, such as warmer temperatures, thereby limiting the decomposition response to climate change Malcolm et al 2008;Andrews et al 2000;Lipson and Schmidt 2004). Although the importance of these biological responses may vary across systems, current biogeochemical models do not account for them at all.…”
Section: Challenges With Current Modelsmentioning
confidence: 96%
“…As a result, microbes are expected to mediate decomposition responses to global changes, such as climate warming (Bardgett et al 2008). Changing climatic conditions will affect the physiology of microbial communities, which may lead to changes in the rates of biogeochemical processes under microbial control Malcolm et al 2008). It is therefore essential to account for the response of microbial communities to environmental parameters in order to predict feedbacks between global change and decomposition processes.…”
mentioning
confidence: 99%